Enhancing Career Development through Alumni Engagement Platforms: An Analytical - R. Deepika,; Dr. K. Santhi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Networking, mentorship and skills development are inextricably linked to alumni engagement platforms and play an important role in career growth. Such platforms help students and alumni to have direct access to the professional world by getting connected with industry knowledge, job openings, and expertise. Such networks help alumni connect with students and, thereby, enhance preparation for careers, encourage the sharing of industry insights, and expose students to real professional settings. Some of the issues include lack of user participation, data privacy concerns, and problems in institutional integration. This paper identifies the effects of alumni engagement platforms on career development, the important characteristics that makes a platform effective, the challenges that it faces, and the possible ways through which its effectiveness can be maximized. A case study methodology has been used in which best practices from some successful ones are portrayed and highlighted to give significance to these practices in modern career development.
Keywords: Alumni engagement; career development; mentorship; networking; skill enhancement; digital platforms